The effective manager - Andres, Tomas Quintin D. (New Day Publishers of the Christian Literature Society of the Philippines, 1995)
A distillation of the best management theories and practices, this book was written to teach, integrate, and infuse the proper knowledge, attitudes, skills, habits and values to all people who will be managing people to attain organizational, national as well as personal objectives.